Encouraging Studentsâ€™ Understanding on Learning Phonology Through Native Speakersâ€™ Videos on YouTube - Rabi’ah; Baidawi, Achmad (PANYONARA: Journal of English Education, 2023)
The goal of teaching and learning in the class is to make the students understand the material. The goal can be reached if the learners are highly motivated to learn and the lecturer can deliver the material. Moreover, in English phonology, to make the students more understand and interested in learning it, the lecturers can use some media, like videos on YouTube, to support their teaching. So the students can comprehend English phonology entirely. The study is mainly intended to find the use of native speakers’ videos in encouraging the students’ understanding of learning English phonology and students’ responses to those strategies. The design of the study was descriptive. The data were collected through classroom observation and a questionnaire. The research respondents were the 36 students of the English teaching-learning program. The result showed that using native speakers’ videos on YouTube can encourage students’ understanding of English phonology. So, using native speakers’ videos in teaching English phonology is well-recommended.